China-origin G1 group isolate FPV072 exhibits higher infectivity and pathogenicity than G2 group isolate FPV027 - Xie, Qiaoqiao; Sun, Zhen; Xue, Xiu; Pan, Yajie; Zhen, Shuye; Liu, Yang; Zhan, Jiuyu; Jiang, Linlin; Zhang, Jianlong; Zhu, Hongwei; Yu, Xin; Zhang, Xingxiao (Frontiers in Veterinary Science, 2024)
Introduction Feline parvovirus (FPV), a single-stranded DNA virus, is accountable for causing feline panleukopenia, a highly contagious and often lethal disease that primarily affects cats. The epidemiology prevalence and pathogenicity of FPV in certain regions of China, however, remains unclear. The aim of this research was to investigate the epidemiology of FPV in different regions of China in 2021 and compare its infectivity and pathogenicity. Methods In this research, a total of 36 FPV strains were obtained from diverse regions across China. Phylogenetic analysis was performed based on the VP2 and NS1 sequences, and two representative strains, FPV027 and FPV072, which belonged to different branches, were selected for comparative assessment of infectivity and pathogenicity. Results and discussion The results revealed that all strains were phylogenetically classified into two groups, G1 and G2, with a higher prevalence of G1 strains in China. Both in vitro and in vivo experiments demonstrated that FPV072 (G1 group) exhibited enhanced infectivity and pathogenicity compared to FPV027 (G2 Group). The structural alignment of the VP2 protein between the two viruses revealed mutations in residues 91, 232, and 300 that may contribute to differences in infectivity and pathogenicity. The findings from these observations will contribute significantly to the overall understanding of the molecular epidemiology of FPV in China and facilitate the development of an effective FPV vaccine.